Pengelolaan arsip digital: Tantangan dan strategi di era transformasi digital - Nurkarimah, Ika (Maliki Interdisciplinary Journal, 2025)
The digital era has driven the transformation of archival systems from analog to digital formats. Digital archiving aims to enhance efficiency in document management, storage, and accessibility. However, implementing electronic archive systems also presents several challenges, including the surge in data volume, rapid information growth, file format complexity, and data security and integrity issues. To address these challenges, organizations must adopt innovative management strategies, such as advanced indexing and search technologies, cloud-based automated systems, file format standardization, and strict data protection policies. With the right approach, institutions can ensure effective digital archive management, improve accessibility, and maintain data security and integrity in the long term.